THE INFLUENCE OF PROFITABILITY, LIQUIDITY, AND THE BOARD OF COMMISSIONERS ON CSR - Widayanti, Leni; Inayati, Nur Isna; Pramono, Hadi; Pratama, Bima Cinintya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The research aim to find out how profitability, liquidity, number of board of commissioners, performance of the board of commissioners, and representation of female board of commissioners affect CSR. The population in this research is General Banking companies listed on the Indonesia Stock Exchange. The sample used is a general banking company registered on the IDX publishes annual and sustainability reports. Forty-two conventional general banking company sectors were sampled in the research for the 2018-2022 period. The method used is the panel regression method. Some of the tests used are the Brush and Pagan Lagrangian Multiplier, Chow, Hausman, and Hypothesis tests. This research hypothesis test shows a positive influence of profitability on CSR Meanwhile, the liquidity and diversity of the board of commissioners do not influence CSR.